Rumpole and the angel of death - Mortimer, John Clifford 1923-2009 (Penguin Books, 1996)
Six stories featuring an English barrister-turned-sleuth. In Rumpole and the Rights of Man, he finds at the European Court of Human Rights that international justice is as fallible as the domestic variety, while Rumpole and the Way Through the Woods involves him in a clash between hunters and animal rights activists.
Keywords: Detective and mystery stories, English; Legal stories, English; Rumpole, Horace (Fictitious character) -- Fiction; London (England) -- Fiction